Quality of life of the patients with chronic cerebrovascular insufficiency and high blood pressure after the stroke patients of SIS «RPC PCM» SAD - Оvodiuk, N. M.; Kravchenko, A. M.; Оvodiuk, M. O. (Journal of Education, Health and Sport, 2017)
The article presents the study of the chronic cerebrovascular insufficiency combined with high blood pressure in patients (civil servants) who recovered from ischemic stroke in comparison with patients who have chronic cerebrovascular insufficiency with high blood pressure but without ischemic stroke in anamnesis. Due to clinical and paraclinical examinations motor, cognitive, mental and volitional disorders were found in both groups. In the group of patients who have ischemic stroke in anamnesis mentioned disorders were more severe. Also it was proved that patients even with slight neurological impairment have authentically lower quality of life.